2018
DOI: 10.1080/2162402x.2018.1465163
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specificity and DTIC before peptide-vaccination differently shape immune-checkpoint expression pattern, anti-tumor functionality and TCR repertoire in melanoma patients

Abstract: We have recently described that DNA-damage inducing drug DTIC, administered before peptide (Melan-A and gp100)-vaccination, improves anti-tumor CD8+ Melan-A-specific T-cell functionality, enlarges the Melan-A+ TCR repertoire and impacts the overall survival of melanoma patients. To identify whether the two Ags employed in the vaccination differently shape the anti-tumor response, herein we have carried out a detailed analysis of phenotype, anti-tumor functionality and TCR repertoire in treatment-driven gp100-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
(95 reference statements)
3
6
0
Order By: Relevance
“…The transcriptional analysis presented here corroborates the comprehensive multiparametric analyses we conducted on Ag-specific PD1 + CD28 − and PD1 + CD28 + CD8 + T-cell clones in our prior studies [ 26 , 27 ]. Consistent with their transcriptional profiles, we observed that Ag-specific PD1 + CD28 − T cells express the highest levels of ICOS, directly implicated in their high polyfunctionality, despite concomitant high expression of inhibitory receptors PD1, LAG-3, and TIM-3 [ 26 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The transcriptional analysis presented here corroborates the comprehensive multiparametric analyses we conducted on Ag-specific PD1 + CD28 − and PD1 + CD28 + CD8 + T-cell clones in our prior studies [ 26 , 27 ]. Consistent with their transcriptional profiles, we observed that Ag-specific PD1 + CD28 − T cells express the highest levels of ICOS, directly implicated in their high polyfunctionality, despite concomitant high expression of inhibitory receptors PD1, LAG-3, and TIM-3 [ 26 ].…”
Section: Resultssupporting
confidence: 86%
“…By taking advantage of a panel of CD8 + Ag-specific (Melan-A + or gp100 + ) T-cell clones isolated from the peripheral blood of melanoma patients, we recently reported that the inhibitory effect of PD1 is associated with the co-expression of CD28 [ 23 , 26 , 27 ], consistent with earlier studies [ 18 ]. Indeed, as illustrated in Fig.…”
Section: Resultssupporting
confidence: 82%
“…It is becoming more apparent, however, that more than just overexpression of wildtype peptide sequences from melanoma cells is needed to induce effective anti-tumor responses from tolerant or low-affinity T cells. Hence, the use of checkpoint inhibitors, such as anti-PD1/PD-L1 and anti-CTLA-4, and adjuvants in combination with selfantigen cancer vaccines is almost requisite (76,77). Currently, identification of neo-antigens broadly expressed by melanomas is an area of intense research.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…While neoantigens expressed by melanoma cells would be the most immunogenic, that is most likely to expand cytotoxic T cells, self‐antigens expressed at high levels could potentially break tolerance and activate low‐affinity CD8+ T cells. To induce effective anti‐tumour responses from such tolerant or low‐affinity T cells, the use of checkpoint inhibitors or a combination with self‐antigen cancer vaccines may be necessary 100 …”
Section: Antigens Used In Tcr Against Melanomamentioning
confidence: 99%